(x-5)/(3*x)+(6/2*x+1)=0

Simple and best practice solution for (x-5)/(3*x)+(6/2*x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-5)/(3*x)+(6/2*x+1)=0 equation:


D( x )

3*x = 0

3*x = 0

3*x = 0

3*x = 0 // : 3

x = 0

x in (-oo:0) U (0:+oo)

(x-5)/(3*x)+(6/2)*x+1 = 0

(x-5)/(3*x)+3*x+1 = 0

(x-5)/(3*x)+((3*x)^2)/(3*x)+(1*3*x)/(3*x) = 0

9*x^2+x+1*3*x-5 = 0

9*x^2+x+3*x-5 = 0

9*x^2+4*x-5 = 0

9*x^2+4*x-5 = 0

9*x^2+4*x-5 = 0

DELTA = 4^2-(-5*4*9)

DELTA = 196

DELTA > 0

x = (196^(1/2)-4)/(2*9) or x = (-196^(1/2)-4)/(2*9)

x = 5/9 or x = -1

(x+1)*(x-5/9) = 0

((x+1)*(x-5/9))/(3*x) = 0

((x+1)*(x-5/9))/(3*x) = 0 // * 3*x

(x+1)*(x-5/9) = 0

( x+1 )

x+1 = 0 // - 1

x = -1

( x-5/9 )

x-5/9 = 0 // + 5/9

x = 5/9

x in { -1, 5/9 }

See similar equations:

| (8x+9)(7x^2+9x+9)= | | (5)/(6)x=-15 | | 5t-t-7=3t-4 | | 3/4(-4y-8x+4z) | | 6(2q+1)=9q-12 | | (7x^2-8x-10)(x-9)= | | 5x=4x-3/4 | | 3/5*10x | | 8.4o-6.8=14.3+6.3o | | 5+4y=2y-13 | | 10m+16n=140 | | -2x^4y^2= | | -27x-9y=18 | | N^2+5n-266=0 | | 2(3x-2)-5x=5-2x | | X-(45)=16 | | (-2x^4y^2)= | | 73-5x=40x+23 | | 0=x^5+4x^4+4x^3 | | (n-5)*8=16 | | N^2+5n-265=0 | | 2x+8=8x-5 | | 6x^2+7x+3=26 | | x-3y=19 | | 36/9*2+6 | | 3t-7=-2t+38 | | y^2+4y^1+2y^0=0 | | -6x-34=3x+11 | | 17g+3=11g+3g | | 13x^2=3x | | -7x-33=2x+12 | | y^2+3y^1+9y^0=0 |

Equations solver categories